MENGUJI KESETIAAN PELANGGAN AYAM SAWCE MASA PANDEMI COVID 19 PADA GENERASI Z - Alfi Para Alfarina; Dwi Syifa Aprilian (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study is to look at the loyalty of Sawce Chicken customers duringthe Covid 19 pandemic in generation Z by measuring customer loyalty such asmeasuring behavior, measuring maintenance costs, measuring satisfaction, measuringbrand liking and measuring commitment.This study uses a descriptive method with a qualitative approach. The populationunder study was Piksi Ganesha polytechnic students who took entrepreneurshipcourses totaling 51 people with purposive sample sampling method. The resultsshowed that Sawce Chicken managed to maintain customer loyalty by showingnumbers in the range of 78.2% - 87.12%.